Emergency front of neck airway: What do trainers in the UK teach? A national survey - Ilyas Qazi; Cyprian Mendonca; Achuthan Sajayan; Adam Boulton; Imran Ahmad (Wolters Kluwer Medknow Publications, 2019)
Background and Aims: Front of neck airway (FONA) is the final step to deliver oxygen in the difficult airway management algorithms. The Difficult Airway Society 2015 guidelines have recommended a standardized scalpel cricothyroidotomy technique for an emergency FONA. There is a wide variability in the FONA techniques with disparate approaches and training. We conducted a national postal survey to evaluate current teaching, availability of equipment, experienced surgical help and prevalent attitudes in the face of a can't intubate, can't oxygenate situation. Material and Methods: The postal survey was addressed to airway leads across National Health Service hospitals in the United Kingdom (UK). In the anesthetic departments with no designated airway leads, the survey was addressed to the respective college tutors. A total of 259 survey questionnaires were posted. Results: We received 209 survey replies with an overall response rate of 81%. Although 75% of respondents preferred scalpel cricothyroidotomy, only 28% of the anesthetic departments considered in-house FONA training as mandatory for all grades of anesthetists. Scalpel-bougie-tube kits were available in 95% of the anesthetic departments, either solely or in combination with other FONA devices. Conclusion: The survey has demonstrated that a majority of the airway trainers in the UK would prefer scalpel cricothyroidotomy as emergency FONA. There is a significant variation and deficiency in the current levels of FONA training. Hence, it is important that emergency FONA training is standardized and imparted at a multidisciplinary level.